2010
DOI: 10.1089/ten.tea.2008.0643
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mesenchymal Stromal Cells on the Osseoinduction of Impaction Grafts

Abstract: Revision total hip replacement has a failure rate of up to 25%. Part of the reason for this high failure is the lack of bone stock. In this study, we investigated whether mesenchymal stromal cells (MSCs) or osteoprogenitors (OPs) contribute to bone formation in impacted allograft or an allograft and hydroxyapatite (HA) combination. Eight samples were inserted in the paraspinal muscles of six sheep, which were allograft or an HA/allograft mix, seeded with autologous MSCs, autologous OPs, or no cells (control), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
1
3
0
1
Order By: Relevance
“…These results were also in agreement with previous studies where scaffolds seeded with MSCs precultured in osteogenic media for very short periods of time showed highest osteoinductivity 33, 34. However, results are in contrast to an ovine model study reported by Korda et al30 where results showed a significant reduction in bone formation in the OPC given group.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results were also in agreement with previous studies where scaffolds seeded with MSCs precultured in osteogenic media for very short periods of time showed highest osteoinductivity 33, 34. However, results are in contrast to an ovine model study reported by Korda et al30 where results showed a significant reduction in bone formation in the OPC given group.…”
Section: Discussionsupporting
confidence: 93%
“…We hypothesized that OPCs would further augment bone growth and bone‐implant contact when compared with autologous MSCs. Our previous studies29, 30 established that MSC expansion in osteogenic culture conditions for 14 days resulted in a population of functionally active secretory osteoblasts that produced significantly increased amounts of ALP and osteocalcin and produced bone mineral at 28 days postculture. Therefore, in this study, MSCs remained in osteogenic culture conditions for 14 days prior to administration in vivo and osteoblastic differentiation was shown with increased alkaline phosphatase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Todos os autores relatados 1,2,3,4,6,9,15 concordam que as células-tronco mesenquimais derivadas da medula óssea humana adulta são um subconjunto de células precursoras multipotenciais. Elas são notáveis por sua capacidade de autoproliferar e se diferenciar ao longo de várias linhagens, incluindo osso, cartilagem, tecido adiposo, células musculares e neurais.…”
Section: Discussionunclassified
“…Others have shown that uninduced MSCs were able to survive in the osteochondral defects and differentiate into osteoblasts, making a contribution to bone regeneration [32]. Studies using animal models have shown that MSCs are osteoinductive [33]. In this regard, we carried out the allogeneic MSCs implantation experiments using the injectable CS/nHAC scaffolds.…”
Section: Discussionmentioning
confidence: 99%